A lack of perceived benefits and a gap in knowledge distinguish the vaccine hesitant from vaccine accepting during the COVID-19 pandemic - Deirdre Robertson; Kieran S. Mohr; Martina Barjakova; Pete Lunn (The Economic and Social Research Institute (ESRI), 2021)
The current strategy to end the COVID-19 pandemic is to achieve herd immunity through mass vaccination. This relies on individuals' willingness to take a vaccine. Yet little is known about how people perceive the risks and benefits of the COVID-19 vaccine. This paper reports the results of a series of interactive tasks that were given to a nationally representative sample of the population to assess how people prioritise risks and benefits, and how much they know about the COVID-19 vaccines. Most individuals see some risks to vaccination, but many hesitant individuals fail to see any benefits. Vaccine hesitant individuals are less knowledgeable about the vaccine, and knowledge is associated with how people perceive benefits and what risks are most salient to them. These differences have a stronger association with intention to be vaccinated than sociodemographic characteristics. Public health communications may need to consider an education campaign to address a significant gap in knowledge.
Keywords: 330; COVID-19; Vaccine Intention; Behavioural Science